Temporal changes in litterfall and potential nutrient return in cocoa agroforestry systems under organic and conventional management, Ghana - Michael Asigbaase; Evans Dawoe; Barry H. Lomax; Sofie Sjogersten (Heliyon, 2021)
Litterfall is a critical link between vegetation and soils by which nutrients are returned to the soils, thus the amount and pattern of litterfall regulates nutrient cycling, soil fertility and primary productivity for most terrestrial ecosystems. We quantified, analyzed and compared macro- and micro-nutrients return through litterfall in organic and conventional cocoa agroforestry systems in Suhum, Ghana. We further assessed the contribution of shade tree species to litterfall and nutrient dynamics. The annual pattern of litterfall was affected by seasonality, with a major peak in the dry season and minor peaks during the rainy season. In terms of annual fractional litterfall, mean leaf litter from shade tree species was significantly higher (50 %) in organic systems (5.0 ± 0.5 Mg ha−1 yr−1) compared to conventional systems (3.3 ± 0.6 Mg ha−1 yr−1). Whereas cocoa leaves (45.0 %) were the predominant fraction of annual litterfall from conventional farms, both shade leaves (40.0 %) and cocoa leaves (39.4 %) dominated litterfall from organic farms. The return of primary macro-nutrients (P and K), secondary macro-nutrients (Ca, Mg and S) and micro-nutrients (Mn, B, Cu, Zn and Mo) via litterfall varied significantly with season, and annual return of nutrients were similar in organic and conventional cocoa systems. Shade tree leaf litter accounted for 30–47 % of annual macro- and micro-nutrient return (except Ni and Zn) in organic cocoa systems versus 20–35 % in conventional cocoa systems. The results emphasize the complementary role of the different shade tree species which compose organic and conventional cocoa systems in nutrient recycling. We conclude that organic management of cocoa agroforestry systems ensure nutrients return similar to those receiving synthetic fertilizer inputs, highlighting its potential to support cocoa production.